Hydrofluoric Acid – Simple Things You May Do Not Know About Something You Are So Habituated To Use - Carpena DDS, MS, PhD, Guilherme; Ballarin DDS, Andressa (Odovtos - International Journal of Dental Sciences, 2015)
Hydrofluoric Acid (HF) acid usually is used to etch the internal surface of the ceramic restoration. This acid increases surface relief in micromechanical bonding of resin cement to ceramic restoration Pre-treatment conditioning with HF in feldspathic ceramic and leucita reinforced glass-ceramic will result in an internal surface with white-opaque appearance. In this brief new perspective article we would discuss some important issues regarding HF use in dentistry.